Studies of Madagascan Ptiliidae (Coleoptera) 3: The genus Acrotrichis including twenty seven new species - Darby, By Michael (Zootaxa, 2014)
This is the third report detailing Ptiliidae collected from forest leaf litter by the Moravian Museum (Brno, Czech Republic) expeditions to Madagascar 2010–2013. After completion of the first draft, which identified 16 new species, more Madagsacan Acrotrichis, collected at earlier dates, were found in the Natural History Museum in London (BMNH). These included 17 unpublished new species determined by Colin Johnson in 1969, 7 of which proved to be the same as those in the Czech material. The decision was taken, therefore, to broaden the scope of the report to include all the mounted Madagascan material in the Museum and to use Johnson’s ms names to avoid potential future confusion. 27 new species are described and figured: Acrotrichis absona sp. n.; A. barclayi sp. n.; A. bibula sp. n.; A. boothi sp. n.; A. clareae sp. n.; A. colini sp. n.; A. cuspida sp. n.; A. difficilis sp. n.; A. exigua sp. n.; A. hammondi sp. n.; A. heissi sp. n.; A. hova sp. n.; A. impressa sp. n.; A. lacrimosa sp. n.; A. lauta sp. n.; A. loganovi sp. n.; A. magnifica sp. n.; A. malitiosa sp. n.; A. obscura sp. n.; A. perexigua sp. n.; A. perfida sp. n.; A. strenua sp. n.; A. subafricana sp. n.; A. tampoketsae sp. n.; A. terminalis sp. n.; A. truncata sp. n. and A. tuberosa sp. n., and new data recorded for six others: a. africana Johnson, A. africanoides Johnson, A. cursitans (Nietner), A. discoloroides Johnson, A. minuscula Johnson, and A. superbioides Johnson. New criteria for assessing speciation in Acrotrichis are suggested, the definition of subgenera discussed and a key to all the known species from the island provided.